The Management of Transalevolar Surgery Teeth with Pulpal Polyps Condition - Bayu Vava Violeta; Bambang Tri Hartomo (Fakultas Kedokteran Gigi Universitas Hang Tuah, 2020)
Background: The failure of intra-alveolar tooth extraction in cases of tooth extraction with complications is generally resolved by performing transalveolar tooth extraction. The open method of tooth extraction involves surgery by cutting the tooth or bone. Flap creation and partial removal of alveolar bone, refinement of alveolar bone, curettage, and suturing are the principles of this extraction method. The planning of the stages of the transalveolar extraction method must be made as carefully as possible to avoid complications of tooth extraction. Tooth extraction treatment in dental practice can be carried out due to various causes, including caries. Pulp polyps or also known as chronic hyperplastic pulpitis is another form of irreversible pulpitis in the chronically inflamed pulp so that the pulp tissue appears to the occlusal surface. Treatment in cases of pulp polyps varies widely depending on the remaining tooth crown wall. The usual treatments for polyps pulp patients are root canal treatment (RCT), pulpotomy to extraction. The transalveolar extraction method is performed by first taking a portion of the bone supporting the tooth. Objective: Knowing the treatment management of polyp pulp extraction with transalveolar surgery methods, indications and contraindications for transalveolar surgery and knowing the correct medical selection in cases of transalveolar surgical extraction of teeth with polyp pulp. Discussion: Chronic hyperplastic pulpitis or pulp polyp is a pathological condition that attacks vital pulp tissue so that it experiences a chronic inflammation as a defense response from the body to the pulp tissue against bacterial infection. The term use of the term chronic hyperplastic pulpitis occurs due to granulation of the pulp tissue covered with epithelial tissue due to chronic infection. The management of cases of pulp polyps for which restoration is no longer possible is to remove them. Extraction is the last step that can be done if restoration measures do not eliminate the source of infection. The transalveolar extraction procedure of the teeth located in the mandible is preceded by asepsis and anesthesia and removal of the polypoid tissue. Conclusion: In several cases of brittle teeth, extraction by intraalveolar method often failed so that it needs to be extracted by transalveolar method. Management of extraction with polyp pulp includes removal of the polypoid tissue first before extraction. The administration of medical therapy with the antibiotic amoxicillin 500 mg for 5 days, paracetamol for 5 days and dexamethasone for 3 days can control the patient's pain and help the healing process quickly.